2015
DOI: 10.1016/j.eururo.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Cumulative Analysis of Oncologic and Functional Outcomes After Robot-assisted Radical Cystectomy

Abstract: Context: Although open radical cystectomy (ORC) is still the standard approach, laparoscopic radical cystectomy (LRC) and robot-assisted radical cystectomy (RARC) are increasingly performed.Objective: To report on a systematic literature review and cumulative analysis of pathologic, oncologic, and functional outcomes of RARC in comparison with ORC and LRC.Evidence acquisition: Medline, Scopus, and Web of Science databases were searched using a free-text protocol including the terms robot-assisted radical cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
129
4
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(158 citation statements)
references
References 100 publications
12
129
4
13
Order By: Relevance
“…The rate for RARC seems high, especially considering the Pasadena Consensus Panel recommendation of <7% PSM rate for RARC [21]. However, we believe our findings reflect our practice of not routinely performing simultaneous urethrectomy unless there is tumour in the urethra because this increases morbidity.…”
Section: Discussioncontrasting
confidence: 53%
“…The rate for RARC seems high, especially considering the Pasadena Consensus Panel recommendation of <7% PSM rate for RARC [21]. However, we believe our findings reflect our practice of not routinely performing simultaneous urethrectomy unless there is tumour in the urethra because this increases morbidity.…”
Section: Discussioncontrasting
confidence: 53%
“…Disease-specific survival (DFS) was 79-96%, 67-76% and 53-74%, respectively (21). However, only 6/18 series (33%) reported a mean follow-up >36 months (21). On the other hand, Raza et al reported the long-term oncological outcomes using the IRCC database (11).…”
Section: Discussionmentioning
confidence: 99%
“…At 1, 3 and 5 years, OS was 82-90%, 61-80% and 39-66%, respectively. Disease-specific survival (DFS) was 79-96%, 67-76% and 53-74%, respectively (21). However, only 6/18 series (33%) reported a mean follow-up >36 months (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective video review has been used in open 9 and laparoscopic radical prostatectomy 10 to identify surgical steps correlated with potency and technical errors leading to positive surgical margin, respectively. Robot-assisted radical cystectomy (RARC) is becoming increasingly used and is under close scrutiny with regards to complications, [11][12][13] such as strictures at the uretero-ileal anastomosis. These may require further endoscopic or surgical intervention and represent a potentially preventable complication of RARC.…”
Section: Introductionmentioning
confidence: 99%